State estimation in networked control systems with a real-time transport protocol - Fang Jin; Long Ma; Chenming Zhao; Qingquan Liu (Systems Science & Control Engineering)
This paper investigates the state estimation problem for linear time-invariant systems where sensors and controllers are connected by a stationary memoryless digital communication channel. Time delay, packet dropout, and data rate limitation occur simultaneously in such a channel. We discuss observability of such systems under communication constraints. A real-time transport protocol (RTP) is used for data transmission. A quantization, coding, and control scheme on the basis of RTP is proposed in order to overcome such difficulties. Sufficient conditions for observability are provided in this case. Our result contains some existing results, and shows that there exists the inherent tradeoff between control and communication costs. Illustrative examples are given to demonstrate the effectiveness of the proposed quantization, coding, and control scheme.